2008
DOI: 10.1002/ptr.2445
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial potential of Antarctic lichens against human pathogenic Gram‐positive bacteria

Abstract: Extracts from five Antarctic lichens (L3, Stereocaulon alpinum; L5, Ramalina terebrata; L6, Caloplaca sp.; L8, Lecanora sp.; and L17, Caloplaca regalis) were tested for antimicrobial activities against several clinically important microbes by disk diffusion. The minimum inhibitory concentration (MIC) of each extract was determined by a broth dilution method. Extracts from L3, L5, L6 and L8 were active against two Gram(+) strains. B. subtilis was more sensitive to lichen extracts (except L5) than S. aureus. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 9 publications
(10 reference statements)
3
26
0
Order By: Relevance
“…These results against S. aureus are similar to many other studies (Gulluce et al, 2006;Paudel et al, 2008Paudel et al, , 2012Srivastava et al, 2013). We found that all crude extracts of the tested lichen species except for Lobaria pulmonaria and Umbilicaria mammulata were found to be active against S. aureus.…”
Section: Discussionsupporting
confidence: 92%
“…These results against S. aureus are similar to many other studies (Gulluce et al, 2006;Paudel et al, 2008Paudel et al, , 2012Srivastava et al, 2013). We found that all crude extracts of the tested lichen species except for Lobaria pulmonaria and Umbilicaria mammulata were found to be active against S. aureus.…”
Section: Discussionsupporting
confidence: 92%
“…During our previous preliminary screening study (Paudel et al, 2008b), the methanol extract of R. terebrata showed antibacterial activity against Gram-positive pathogenic bacteria. The further work of isolation of bioactive compounds gave fi ve compounds as described above.…”
Section: Antibacterial Activities Of the Isolated Compoundsmentioning
confidence: 97%
“…In order to prevent spreading of infection by antibiotic resistant microbes, scientists have been conducting intensive researches to determine new alternative antimicrobial agents (Paudel et al, 2008;Özkan et al, 2015). Huge number of studies presented that natural products have been used for hundreds of years to treat several diseases caused by bacteria, fungi, viruses and parasites (Jones, 1996;Onbaşılı et al, 2011;Onbaşlı et al, 2013).…”
Section: Introductionmentioning
confidence: 99%